ACSeg: Automated 3D Cytoplasm Segmentation in Soft X-Ray Tomography [Jurkat T cell data] - Aydogdu-Erozan, Ayse; Heuveline, Vincent; Weinhardt, Venera (Universität, 2024)
The structure of cells is a key to understanding cellular function, diagnosing diseases, and developing new treatments. Soft X-ray tomography is uniquely used to access 3D cellular structure of various cells at statistically significant sample sizes. These datasets are reconstructed 3D volumes obtained by soft X-ray tomography on Jurkat T cells. The data is organized in individual *.tif files.
Gefördert durch: EU Research and Innovation Act: 101017116; xcellence Strategy of the Federal and State Governments of Germany: FIEMS
Gesehen am 19.03.2025
Keywords: Forschungsdaten; Datenbank